Why Didn't You Reach Out? - Rae Ann Van Beers (Canadian Society for Studies in Education, 2021)
Individuals who exist with depression repeatedly hear the appeal of 'reach out'. What is left unacknowledged by that advice are the many times that these exact individuals have sought help from others, only to be met with obstacles. Using poetic autoethnography, I reflect on my own reaching out attempts, most recently during my doctoral studies. The poetic dialogues are shared in the hopes that they may provide support and encouragement to other graduate students experiencing depression. By revealing how institutional policies have intersected with and impacted my experiences of depression, I also hope that this contribution will shift our understandings of depression. Instead of viewing depression as isolated within individuals, and therefore a solitary problem, I wish to challenge institutions and the individuals within them to see it as an issue of collective well-being that is produced, at least in part, by the systems in which we all exist.